One-pot syntheses of irida-polycyclic aromatic hydrocarbons - Hu, Yu Xuan (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Metalla-analogues of polycyclic aromatic hydrocarbons (PAHs) have captivated chemists with their fascinating structures and unique electronic properties. To date, metallabenzene, metallanaphthalene and metallaanthracene have been reported. Metalla-analogues with more complicated fused rings have rarely been reported. Herein, we have successfully synthesized a series of new iridafluoranthenes and fused-ring iridafluoranthenes ranging from pentacyclic to heptacyclic metallaaromatic hydrocarbons in high yields under mild reaction conditions for the first time. Their photophysical and redox properties were also explored using UV-vis spectroscopy and electrochemistry combined with TD-DFT calculations. The present work may offer an important guideline for the design and construction of new polycyclic metallaaromatic hydrocarbons and metalla-nanographenes.